Dane symboliczne w klasyfikacji oczekiwań pracodawców wobec absolwentów kierunków inżynierskich i menedżerskich - Staniec, Iwona; Żółtowski, Jan (The Symbolic Data in the Classification of Expectations of Employers for Graduates in Engineering and Management, 2009)
The aim of the deliberations is to classify graduates of various courses due to the assessment of their skills by employers, and pointing out common characteristics and features that diverse different courses. An original approach in the article refers to using rates as a specific type of variables. The results of the classification for the data presented allow to obtain homogeneous groups of courses and to clearly define common and differing features. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 231-239